Impact of an evidence-based intervention on urinary catheter utilization, associated process indicators, and infectious and non-infectious outcomes. Issue 2 (October 2020) - Schweiger, A.; Kuster, S.P.; Maag, J.; Züllig, S.; Bertschy, S.; Bortolin, E.; John, G.; Sax, H.; Limacher, A.; Atkinson, A.; Schwappach, D.; Marschall, J.
Summary: Background: Multi-centre intervention studies tackling urinary catheterization and its infectious and non-infectious complications are lacking. Aim: To decrease urinary catheterization and, consequently, catheter-associated urinary tract infections (CAUTIs) and non-infectious complications. Methods: Before/after non-randomized multi-centre intervention study in seven hospitals in Switzerland. Intervention bundle consisting of: (1) a concise list of indications for urinary catheterization; (2) daily evaluation of the need for ongoing catheterization; and (3) education on proper insertion and maintenance of urinary catheters. The primary outcome was urinary catheter utilization. Secondary outcomes were CAUTIs, non-infectious complications and process indicators (proportion of indicated catheters and frequency of catheter evaluation). Findings: In total, 25, 880 patients were included in this study [13, 171 at baseline (August–October 2016) and 12, 709 post intervention (August–October 2017)]. Catheter utilization decreased from 23.7% to 21.0% ( P =0.001), and catheter-days per 100 patient-days decreased from 17.4 to 13.5 ( P =0.167). CAUTIs remained stable at a low level with 0.02 infections per 100 patient-days (baseline) and 0.02 infections (post intervention) ( P =0.98). Measuring infections per 1000 catheter-days, the rate was 1.02 (baseline) and 1.33 (post intervention) ( P =0.60). Non-infectious complications decreased significantly, from 0.79 to 0.56 events per 100 patient-days ( P <0.001), and from 39.4 to 35.4 events per 1000 catheter-days ( P =0.23). Indicated catheters increased from 74.5% to 90.0% ( P <0.001). Re-evaluations increased from 168 to 624 per 1000 catheter-days ( P <0.001). Conclusion: A straightforward bundle of three evidence-based measures reduced catheter utilization and non-infectious complications, whereas the proportion of indicated urinary catheters and daily evaluations increased. The CAUTI rate remained unchanged, albeit at a very low level.